Anterior Minithoracotomy: a Safe Approach for Surgical ASD Closure & ASD Device Retrieval - Wadhawa,Vivek (2017)
Abstract Objective: Midline sternotomy is the preferred approach for device migration following transcatheter device closure of ostium secundum atrial septal defect. Results of patients operated for device migration were retrospectively reviewed after transcatheter closure of atrial septal defect. Methods: Among the 643 patients who underwent atrial septal defect with closure device, 15 (2.3%) patients were referred for device retrieval and surgical closure of atrial septal defect. Twelve patients underwent device retrieval and surgical closure of atrial septal defect through right antero-lateral minithoracotomy with femoral cannulation. Three patients were operated through midline sternotomy. Results: Twelve patients operated through minithoracotomy did not require conversion to sternotomy. Due to device migration to site of difficult access through thoracotomy, cardiac tamponade and hemodynamic instability, respectively, three patients were operated through midline sternotomy. Mean aortic cross-clamp time and cardiopulmonary bypass time were 28.1±17.7 and 58.3±20.4 minutes, respectively. No patient had surgical complication or mortality. Mean intensive care unit and hospital stay were 1.6±0.5 days and 7.1±2.2 days, respectively. Postoperative echocardiography confirmed absence of any residual defect and ventricular dysfunction. In a mean follow-up period of six months, no mortality was observed. All patients were in New York Heart Association class I without wound or vascular complication. Conclusion: Minithoracotomy with femoral cannulation for cardiopulmonary bypass is a safe-approach for selected group of patients with device migration following transcatheter device closure of atrial septal defect without increasing the risk of cardiac, vascular or neurological complications and with good cosmetic and surgical results.